Efficacy and cost-effectiveness of Internet-delivered cognitive-behavior therapy for children and adolescents with body dysmorphic disorder: study protocol for a randomized controlled trial - Lorena Fernández de la Cruz; Anita Birovecz; Per Andrén; Karin Melin; Kristina Aspvall; Matti Cervin; Erik Andersson; Maria Silverberg-Mörse; Martina Gumpert; Frida Wickberg; Matteo Bottai; Eva Serlachius; et al. (Trials, 2026)
Abstract Background Body dysmorphic disorder (BDD) is a prevalent and impairing mental disorder that typically onsets in adolescence. Cognitive-behavior therapy (CBT) may be effective for adolescent BDD, although the supporting evidence is currently limited. CBT for BDD is a highly specialized treatment, creating a considerable gap in access to care for young people. Therapist-guided Internet-delivered CBT (ICBT) may help bridge this gap. The primary aim of this study is to determine the efficacy of a therapist-guided ICBT program for children and adolescents with BDD versus an active comparator. Secondary aims are to examine the 6-month durability of the treatment effects and to evaluate its relative cost-effectiveness from multiple perspectives. Methods This is a 3-site superiority randomized controlled trial including 154 young people (12–17 years) with BDD recruited throughout Sweden. Participants are randomized 1:1 to 12 weekly modules of either therapist-supported ICBT primarily based on exposure with response prevention or an active comparator consisting of therapist-supported Internet-delivered relaxation training. Data will be collected at baseline, mid-treatment, post-treatment, and 1 month (primary endpoint), 3 months, and 6 months post-treatment. The primary outcome is BDD symptom severity measured with the Yale-Brown Obsessive-Compulsive Scale Modified for Body Dysmorphic Disorder, Adolescent version. All study personnel who can be blinded to study aims/hypotheses and group allocation will be blinded. Assessors conducting post-treatment and follow-up assessments will be external to the research team and blinded to study aims/hypotheses and group allocation at all assessment points. Analyses will be conducted according to the intention-to-treat principle and will follow a pre-specified statistical and health economic analysis plan. Discussion Participant recruitment started on 22 February 2024 and is currently ongoing. Data analysis for the primary aim will commence after the last participant reaches the primary endpoint. Trial registration ClinicalTrials.gov NCT06262412. Registered on 16 February 2024, https://clinicaltrials.gov/study/NCT06262412 .